Occupational transmission of an Orthopoxvirus infection during an outbreak in a colony of Macaca tonkeana in Lazio Region, Italy, 2015. (7th March 2018) - Puro, V.; Fusco, F. M.; Castilletti, C.; Carletti, F.; Colavita, F.; Agrati, C.; Di Caro, A.; Capobianchi, M. R.; Ippolito, G.
Summary: Orthopoxviruses spill over from animal reservoirs to accidental hosts, sometimes causing human infections. We describe the surveillance and infection control measures undertaken during an outbreak due to an Orthopoxvirus occurred in January 2015 in a colony of Macaca tonkeana in the province of Rieti, Latio, Italy, which caused a human asymptomatic infection. According to the epidemiological investigation, the human transmission occurred after an unprotected exposure. The contacts among wild, captive and domestic animals and humans, together with decreased immunity against Orthopoxviruses in the community, may put animal handlers at risk of infection, especially after the cessation of smallpox vaccination. To reduce these threats, standard precautions including respiratory hygiene and transmission‐based precautions should be carefully applied also in veterinary medicine.